(untitled) (Training and Practice : Journal of Educational Sciences, 2022)
Internationally and domestically, educational research focuses on the educational challenges of the 21st century, and how to teach and motivate today’s generation most effectively. Teaching methods are sometimes underdeveloped and do not adapt to the rapidly evolving world or to the interest of children. The literature places significant emphasis on gamification as a motivational factor. We need a motivational tool that arouses and then maintains interest for a long time, and is realized in an environment that is used by students. In our study, we show how the gamification we used, contributed to the birth of a mobile application, MotivApp. The mobile application aims to motivate students to learn and reduce stress at school.